Expanding Role of T Cells in Human Autoimmune Diseases of the Central Nervous System - Pilli, Deepti; Zou, Alicia; Tea, Fiona; Dale, Russell C.; Brilot, Fabienne (Frontiers in Immunology, 2017)
It is being increasingly recognised that a dysregulation of the immune system plays a vital role in neurological disorders and shapes the treatment of the disease. Aberrant T cell responses, in particular, are key in driving autoimmunity and have been traditionally associated with multiple sclerosis. Yet, it is evident that there are other neurological diseases in which autoreactive T cells have an active role in pathogenesis. In this review, we report on the recent progress in profiling and assessing the functionality of autoreactive T cells in central nervous system autoimmune disorders that are currently postulated to be primarily T cell-driven. We also explore the autoreactive T cell response in a recently emerging group of syndromes characterized by autoantibodies against neuronal cell-surface proteins. Common methodology implemented in T cell biology is further considered as it is an important determinant in their detection and characterization. An improved understanding of the contribution of autoreactive T cells expands our knowledge of the autoimmune response in central nervous system disorders and can offer novel methods of therapeutic intervention.